Anselm's other argument - Smith, Arthur David (Harvard Univ. Press, 2014)
The modal ontological argument -- Anselm's understanding of conceivability -- Anselm's understanding of possibility -- The proslogion iii argument -- Arguments in the reply to Gaunilo -- Anselm's other argument -- An assessment of the argument